ELASTISITAS HUKUM ISLAM DALAM MERESPONS PERUBAHAN SOSIAL - Junaidi Lbs (Jurnal Madania, 2014)
The present paper will describe elasticity of Islamic law in responding global and social change. The Islamic law is not only a law given by the will of Lord to all human being, but it has been also a dynamic and flexible law which came gradually in accordance with development of muslim societies through ijtihad which interpreteds the sacred text, naş, compares analogically a new case that there is no legal recommended with a legal recommended case based on the mean of Islamic law. Historically, through considering public interest and social change logic, the government has a capable of declaring a decision that has relation to the naş argument by political power if needed. it was followed, for instance, that a male muslim who was allowed to marry a christian woman was forbidden in Umar bin Khatab era